Pengembangan Media Pembelajaran Berbasis Web pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 1 Lembah Melintang - Harry Pratama Figna; Kasman Rukun; Dedy Irfan (Universitas Negeri Padang, 2019)
This research aims to get web-based learning media with a valid, practical, and effective on subjects the basic computer and network. This web-based learning media designed to improve the understanding of students thus increasing the learning results. This research uses research methods Research and Development (R and D) with 4-D development procedures (Define, Design, Develop, Disseminate). Data analysis techniques using descriptive analysis techniques for describing validity, practicalities, and web-based learning media efetivitas. The results obtained from the research of development: (1) the validity of a web-based learning media declared valid on aspects of media and materials, (2) a web-based learning media practicalities based on the response of teachers and students expressed very practical, (3) the effectiveness of web-based learning media declared effective in improvinglearning outcomes. Based on the findings of this study it was concluded that a web-based learning media declared valid, practical, and effective way to used as learning materials on subjects the basic computer and network.